Dendritic cell‐based therapeutic vaccine elicits polyfunctional HIV‐specific T‐cell immunity associated with control of viral load. Issue 9 (September 2014) - Lévy, Yves; Thiébaut, Rodolphe; Montes, Monica; Lacabaratz, Christine; Sloan, Louis; King, Bryan; Pérusat, Sophie; Harrod, Carson; Cobb, Amanda; Roberts, Lee K.; Surenaud, Mathieu; Boucherie, Céline; et al.
<x xml:space="preserve">Abstract</x> Efforts aimed at restoring robust immune responses limiting human immunodeficiency virus (HIV)‐1 replication therapeutically are warranted. We report that vaccination with dendritic cells generated ex vivo and loaded with HIV lipopeptides in patients (n = 19) on antiretroviral therapy was well tolerated and immunogenic. Vaccination increased: (i) the breadth of the immune response from 1 (1–3) to 4 (2–5) peptide‐pool responses/patient (p = 0.009); (ii) the frequency of functional T cells (producing at least two cytokines among IFN‐γ, TNF‐α, and IL‐2) from 0.026 to 0.32% (p = 0.002) and from 0.26 to 0.35% (p = 0.005) for CD4+ and CD8+ T cells, respectively; and (iii) the breadth of cytokines secreted by PBMCs upon antigen exposure, including IL‐2, IFN‐γ, IL‐21, IL‐17, and IL‐13. Fifty percent of patients experienced a maximum of viral load (VL) 1 log10 lower than the other half following antiretroviral treatment interruption. An inverse correlation was found between the maximum of VL and the frequency of polyfunctional CD4+ T cells (p = 0.007), production of IL‐2 (p = 0.006), IFN‐γ (p = 0.01), IL‐21 (p = 0.006), and IL‐13 (p = 0.001). These results suggest an association between vaccine responses and a better control of viral replication. These findings will help in the development of strategies for a functional cure for HIV infection.